Teachers’ awareness of differentiated learning dimensions for students with special educational needs in Kuwait - Alqallaf, Bader Jassim; Alsahou, Hamed Jassim; Almusawi, Hashemiah Mohammad (Journal of Educational and Psychological Sciences, 2020)
The current study aims to identify the awareness of teachers of special education programs in the state of Kuwait of differentiated learning or what is known as “pedagogical difference” based on four components. The four components are the foundation of individual differences, planning and preparation, instructional strategies, and learning environment. A questionnaire was developed and distributed in 18 schools that provide special education programs (9 male schools and 9 female schools) in which 158 respondents completed the questionnaire. The study concluded the following results: The teachers have a high level of awareness of differentiated learning and its components. The dimension of learning environment was the highest mean (M =4.39), followed by the dimension of learning strategies (M= 4.37) then the dimension of individual differences (M= 4.22) and the dimension of planning and preparation (M =4.03). Also, statistical differences were emerged according to some demographic variables such as years of experience, academic qualifications, taught course, type of disability. No statistical differences were found based on gender and school level. These findings are discussed according to the previous empirical works and literature review followed by some implications and suggestions.